2019
DOI: 10.1097/prs.0000000000005707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Sex, and Body Mass Index on the Thickness of the Gluteal Subcutaneous Fat: Implications for Safe Buttock Augmentation Procedures

Abstract: Background: The deep intramuscular approach during buttock augmentation with fat grafting has been associated with a significantly increased risk for pulmonary fat embolism. This study was designed to provide guidance for injection into the subcutaneous fat. Methods: The authors investigated 150 Caucasian individuals with an equal distribution of men and women (n = 75 each) and a balanced distribution of age (n = 30 per decade: 20 to 29, 30 to 39, 40 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Limiting skin contact minimizes the possibility of surface compression by the transducer and allows more accurate surface length measurements. Additionally, as described in previous studies, [16][17][18][19][20] having no contact between the skin surface and the transducer is of crucial importance when measuring soft tissue thickness or the depth of neurovascular structures.…”
Section: Discussionmentioning
confidence: 97%
“…Limiting skin contact minimizes the possibility of surface compression by the transducer and allows more accurate surface length measurements. Additionally, as described in previous studies, [16][17][18][19][20] having no contact between the skin surface and the transducer is of crucial importance when measuring soft tissue thickness or the depth of neurovascular structures.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, injection of only a small amount of fat can cause excessive pressure in the narrow space around the vagina. 18 , 20 To summarize, in the absence of solid evidence obtained by performing an anatomical examination, the vaginal fat grafting procedure was the most likely cause of the multiple-organ fat embolisms. Further research is needed to elucidate the anatomical mechanism underlying this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…18 More recently, many surgeons have been avoiding injecting fat intramuscularly due to the increased risk of fat emboli. 21 Frank et al recently published two formulas-one for men and another for women-to estimate the thickness of gluteal subcutaneous fat in an effort to further reduce the chance of intramuscular injection. This study also showed statistically significant correlations of both high BMI and increased age with increased thickness of subcutaneous fat.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…This study also showed statistically significant correlations of both high BMI and increased age with increased thickness of subcutaneous fat. 21 According to one systematic review, fewer surgeons perform tunneling, a technique in which tunnels are created with the cannula prior to applying suction. 18 While the majority of surgeons endorse injecting small aliquots of fat at a time, the quantities reported range from 0.3 to 20 mL, with multiple surgeons reporting 0.3 mL as their maximum aliquot per pass.…”
Section: Operative Techniquesmentioning
confidence: 99%